Ground Behaviors Analysis of a Stope Covered by the Thin Bedrock and Large-Thick Alluvium: A Case Study - Xiaoping Li; Guangchao Zhang; Guangzhe Tao; Chao Wang; Huaixuan Cao; Xipo Zhao; Xianyang Yan; Shibao Shen; Guanglei Zhou (Shock and Vibration)
Support crushing and roof fall accidents frequently occur in the large mining height stope covered by the thin bedrock and large-thick alluvium (TBLA). A comprehensive method including field monitoring, numerical modelling, and theory analysis was performed to investigate the strata movement and its induced ground behaviors of a deep-buried stope under TBLA. The filed measurement results indicated that strong roof periodic weighting phenomenon occurred regularly at an interval of 18–23 m during panel 3301 retreating. During weighting period, dynamic characteristics of hydraulic supports are prominent and characterized by high safety valve opening rate and poor working conditions including tilt down operation and excessive end distance. Additionally, numerical modelling results revealed that the thickness of bedrock affects the movement behaviors of the roof strata and its generated spatial structure significantly. Based on the above results, an integrated control measure was proposed and successfully applied to the test site.